Negotiating in a Foreign Language - Bülow-Møller, Anne Marie (HERMES - Journal of Language and Communication in Business, 1993)
This study examines characteristic features of simulated negotiations between native and non-native speakers. The difficulties encountered by the non-native group are stratified according to footing, where five different layers are found: interpersonal, intergroup, intercultural, interlanguage, and game-frame.